2011
DOI: 10.1117/12.896832
|View full text |Cite
|
Sign up to set email alerts
|

Application of global optimization algorithms for optical thin film index determination from spectro-photometric analysis

Abstract: A large number of parameters is often required to describe optical dispersion laws, and it is only through the use of an appropriate global optimization procedure that an accurate thin film index determination can be achieved. In this paper, we propose to investigate the respective performances of three different optimization algorithms, namely Simulated Annealing, Genetic Algorithm and Clustering Global Optimization and compare results with a commercial software dedicated to thin film index determination. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Besides, the number of pulses outputted by the gyro under significant heading change differs greatly from that computed based on the calibration results under slight heading change. These phenomena are referred to as the course effect [8]. Repeated experiments have shown that new drift occurs under additional disturbance torque.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the number of pulses outputted by the gyro under significant heading change differs greatly from that computed based on the calibration results under slight heading change. These phenomena are referred to as the course effect [8]. Repeated experiments have shown that new drift occurs under additional disturbance torque.…”
Section: Introductionmentioning
confidence: 99%